2019
DOI: 10.1186/s13104-019-4347-4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of anemia and associated factors among pregnant women in Adigrat General Hospital, Tigrai, northern Ethiopia, 2018

Abstract: Objectives Anemia remains a major public health problem in Ethiopia, which causes maternal and fetal severe consequences. In Tigrai, there are limited literatures on prevalence of anemia and associated factors among pregnant women. Thus, a hospital based cross-sectional study was conducted to determine the prevalence and associated factors of anemia in Adigrat General Hospital. Data was analyzed and computed using SPSS version 22. p value = 0.05 at 95% confidence interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
51
5
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 25 publications
14
51
5
2
Order By: Relevance
“…The current study showed that, the prevalence of anemia was 2.18 times higher at third trimester [AOR (95% CI) = 2.18 (1.40 -3.40), P = 0.001] than first trimester. The study finding was well-matched with other studies conducted at Adigrat General Hospital, Northern Ethiopia [5], Southern Ethiopia [6], JigJiga, Eastern Ethiopia [13], Addis Ababa, Ethiopia [27], Southern Ethiopia [31], and Tikur Anbessa Specialized Hospital, Addis Ababa Ethiopia [32]. Pregnant women's birth interval having less than two years [AOR (95% CI) = 2.87 (1.51 -5.44), P = 0.001] were 2.87 times more likely to be anemic compared to those with birth interval more than two years.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The current study showed that, the prevalence of anemia was 2.18 times higher at third trimester [AOR (95% CI) = 2.18 (1.40 -3.40), P = 0.001] than first trimester. The study finding was well-matched with other studies conducted at Adigrat General Hospital, Northern Ethiopia [5], Southern Ethiopia [6], JigJiga, Eastern Ethiopia [13], Addis Ababa, Ethiopia [27], Southern Ethiopia [31], and Tikur Anbessa Specialized Hospital, Addis Ababa Ethiopia [32]. Pregnant women's birth interval having less than two years [AOR (95% CI) = 2.87 (1.51 -5.44), P = 0.001] were 2.87 times more likely to be anemic compared to those with birth interval more than two years.…”
Section: Discussionsupporting
confidence: 88%
“…The present study also showed that, history of blood loses (yes) [AOR (95% CI) = 2.08 (1.04 -4.17), P = 0.03] was statistically significant association with anemia. Findings were similar with the study conducted at Southern Ethiopia [2], Northern Ethiopia [5], Southeast Ethiopia [7], Tigray region, northern Ethiopia [21], and Addis Ababa Ethiopia [32]. Food group eaten 24 hours (1 -4 groups) [AOR (95% CI) = 3.43 (1.84 -6.39), P = 0.001] 3.43 times were more anemic than who are eaten > 8 food groups.…”
Section: Discussionsupporting
confidence: 84%
“…Pregnant women having parasitic infestation were nearly 12 times AOR = 11.886(95% CI 5.606, 25.204) more likely to be anemic than their counterparts. This nding is consistent with studies conducted in Gondar (28), Shire 14, Adigrat (27), and North Shoa (9). This might be due to the reason that parasites attach and injure upper intestinal mucosa and ingest blood.…”
Section: Magnitude Of Anemia In Pregnant Womensupporting
confidence: 91%
“…The possible reasons for the difference may be resulted from geographical variation of factors across different areas. In addition, lower magnitude can be attributed to gradual improvement of life style and living standards, using the iron supplementation ordered by the physician during follow up (23) This study nding showed a slightly higher magnitude than studies conducted in Hawassa (15.3%) (24) ,Tikur Anbesa Specialized Hospital (14.1%) (25), Adama town (11.3%) (26), North Shoa zone (9.7%) (9) and Adigrat General Hospital 7.9% (27). This variation might be due to differences in sample size, study design, study period, study setting, and socio-demographic characteristics.…”
Section: Magnitude Of Anemia In Pregnant Womenmentioning
confidence: 62%
“…This study finding showed a slightly higher magnitude than studies conducted in Hawassa (15.3%) (21) ,Tikur Anbesa Specialized Hospital (14.1%) (22) , Adama town (11.3%)(23), North Shoa zone (9.7%) (9) and Adigrat General Hospital 7.9% (24). This variation might be due to differences in sample size, study design, study period, study setting, and socio-demographic characteristics.…”
Section: Discussioncontrasting
confidence: 56%